Marriage Contracts as a Form of Legal Protection for Married Couples - I Putu Arik Adi Wiguna; Putu Ayu Sriasih Wesna; I Wayan Kartika Jaya Utama (Dinasti Research, 2026)
Article 29(2) of the Marriage Law and Article 139 of the Civil Code do not explicitly regulate the substance of clauses that may be included in a prenuptial agreement, thereby creating ambiguity in the legal norms and leading to multiple interpretations in their application. This study examines two issues: the regulation of clauses in prenuptial agreements for married couples and the role of such clauses in ensuring legal protection for married couples. This study employs a normative legal research method using a statutory and conceptual approach, as well as qualitative analysis of legal materials through a literature review. The results of the study indicate that the regulation of marriage agreement clauses is based on the Civil Code, the Marriage Law, the Compilation of Islamic Law, and Constitutional Court Decision No. 69/PUU-XIII/2015. Based on the principle of freedom of contract, the parties may include clauses regarding the separation of assets or the protection of the parties’ interests, provided they do not conflict with the law, religion, and public morality. The clauses in a marriage contract serve as a means of preventive and repressive legal protection that ensures legal certainty, justice, and public benefit—including the protection of assets, protection in the event of divorce, and protection against third parties through the principle of publicity regarding the registration of marriage contracts.